OP65 Parent Understanding and Management of Rtis in Children: Implications for Health Practitioner Communication. (17th September 2012) - Cabral, CL; Horwood, JP; Hay, AD; Ingram, JC
Abstract : Background: Respiratory tract infections (RTIs) are among the commonest reason parents consult their GP, representing a significant burden on primary health care services. Many of the symptoms associated with RTIs are a cause of anxiety for parents, but they are often unsure when to consult. This study investigated parents' experiences of consulting for RTI in their child as part of a wider TARGET programme to improve the care of children with RTIs. Methods: Parents were recruited through 6 practices in areas of high, middle and low deprivation to capture a range of patient populations. Parents with a child aged between 3 months and 12 years who had consulted for acute RTI within the previous 3 months (excluding children with serious or chronic health problems) were invited to participate. Sampling ensured that parents with younger and older children and parents who were more or less frequent consulters were sampled. Semi-structured interviews explored parent's experience of consulting for RTIs in their children, information and advice needs; and their understanding of RTIs and treatment options. Interviews were audio-recorded, transcribed and imported into NVivo8 for coding. A thematic analysis was conducted using constant comparison techniques. Results: Thirty parents were interviewed and the sample captured a range of socio-economic backgrounds, both single and double parent families, with between 1 and 4 children. Consultation rates ranged from 1 to 24 times per year. New parents often had little knowledge of RTIs in children; felt uncertain about which symptoms might indicate a serious illness; and were surprised at how long a RTI could persist for and how frequently a child could get a RTI, particularly in the first years of life. This was true for parents from all socio-economic backgrounds and with different levels of education. When consulting, parents were often seeking a medical assessment and reassurance. However, parents felt that clinicians were often dismissive and had not properly evaluated the child, often leading to re-consultations. In addition, clinician explanations of diagnosis and treatment recommendations were not well understood by parents, and they remained unclear about how to manage an RTI and when to consult. Conclusion: Parents' poor knowledge and un-realistic expectations in relation to RTIs in children contribute to high rates of consultation. Despite awareness of parental perspectives, there remains a problem with parent-HP communication in relation to key information needed by parents to manage child's illness confidently and know when to consult in future.